Answer:
Verification:
Let's verify all the options to see which is equivalent.
________________________________________________
Option-A:
- 50h(5h + 2) = 250h² - 100h
- => 250h² + 100h = 250h² - 100h
- => 250h² + 100h ≠ 250h² - 100h (False)
________________________________________________
Option-B:
- 50h(5h - 2) = 250h² - 100h
- => 250h² - 100h = 250h² - 100h (True)
________________________________________________
Option-C:
- 50(5h + 2) = 250h² - 100h
- => 250h + 100 = 250h² - 100h
- => 250h + 100 ≠ 250h² - 100h (False)
________________________________________________
Option-D:
- 50(5h - 2) = 250h² - 100h
- => 250h - 100 = 250h² - 100h
- => 250h - 100 ≠ 250h² - 100h (False)
________________________________________________
Hence, Option B is correct.